Analisis Sistem Pengelolaan Keuangan Daerah Dalam Mencapai Kinerja Pembangunan di Kelurahan Bandar Jaya Timur - Anandita Vivian Salsa Billa; Mely Widiyastuti; Olivia Yonata; Yesi Lita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the regional financial management system in achieving development performance in Bandar Jaya Timur Subdistrict. The research method used is descriptive qualitative with data collection through interviews, observation and documentation studies. The research results show that the regional financial management system in Bandar Jaya Timur Subdistrict is not optimal. Budget planning is still not fully participatory, coordination between village and sub-district governments still needs to be improved, and monitoring of budget realization is not carried out regularly. This has an impact on development performance achievements that are not yet optimal, such as basic infrastructure development, developing local economic potential, and improving the quality of public services. To improve development performance, it is recommended that regional governments optimize regional financial management systems by increasing transparency, accountability and community participation in the budget planning, implementation and monitoring processes.